(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
Stock market is a clear indicator of a country’s economic progress. Investors may adjust their investments based on their forecasts of the economy’s future. It serves as a reflection of a country’s economic indicators. Rising stock prices may indicate optimism for future economic expansion and corporate success. Many articles published in various national and international magazines, publications, and websites serve as the foundation for this review paper. Review of articles was conducted, and the review revealed a research gap that concludes inferences based on a literature review. The paper revealed that growth in the stock index is typically regarded as a positive indicator since it shows that investors are optimistic about the state of the economy. A country’s stock market performance is positively correlated with its economic factor.